THE USE OF YOUTUBE VIDEOS IN EFL CLASSROOM - Rafika Nurhidayah (Jurnal Ilmiah Spectral, 2018)
A resourceful English language teacher engaged with technology is desirable in EFL classroom. With the advanced development of technology in language teaching and learning, we have a lot to choose such as YouTube videos. YouTube videos allow English language teacher to access the desirable video content. This study attempts to compile the theory on the use of YouTube videos in EFL classroom. By using the appropriate YouTube videos, teachers will be able to follow the advance technology in order to improve teaching and learning as well as complying current learners’ technological needs.